Reconnecting the missing link : SBY and the democratic party - Yoes, C. Kenawas (2013)
President Yudhoyono's decision to assume the chairmanship of the Democratic Party should not lead to a grimmer future for it and his administration. The personality-oriented mindset of the electorate should provide the impetus to save his party in the 2014 national elections.